All Souls Day : The World War II Battle and the Search for a Lost U.S. Battalion - Pereira, Joseph M.; Wilson, John L. (Military historian) (Book collections on Project MUSE., 2020)
"The reconstruction of a little-known battle during World War II, and the impact it has to this day"--